2005
DOI: 10.1021/ma051116o
|View full text |Cite
|
Sign up to set email alerts
|

A Photoinduced Refractive Index Increase in Poly(methyl methacrylate) Film Doped withN-Acetyl-α-dehydroarylalanine Naphthyl Esters

Abstract: As a result of great demand for advanced optical materials such as plastic optical fiber, 1 the photochemical decrease in refractive index for polymer films has attracted considerable attention for the past decade. [2][3][4] We succeeded in lowering the refractive index of poly-(methyl methacrylate) (PMMA) film (doped with hydroxy-substituted diarylnitrones) by as much as 0.014 (-∆n) by their quantitative photochemical conversions into diarylformamides showing a much weaker π-conjugation. 3 On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Kern et al 33,34 examined the photo-Fries rearrangement based on the polymer, and observed Án D 's in the range from 0.042 to 0.070. Sakurai et al 35 reported that Án D of poly(methyl methacrylate) film doped with N-acetyl--dehydroarylalanine naphthyl ester reached about 0.02. However, it is difficult to apply these materials in the optoelectronics industry, because the photo-chemical reaction is accompanied with release of low-molecular compounds or gases.…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kern et al 33,34 examined the photo-Fries rearrangement based on the polymer, and observed Án D 's in the range from 0.042 to 0.070. Sakurai et al 35 reported that Án D of poly(methyl methacrylate) film doped with N-acetyl--dehydroarylalanine naphthyl ester reached about 0.02. However, it is difficult to apply these materials in the optoelectronics industry, because the photo-chemical reaction is accompanied with release of low-molecular compounds or gases.…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%
“…Two isosbestic points at 235 and 249 nm were observed; this suggests that the photochemical isomerization of calixarene derivatives occurred selectively without any side reaction upon photo-irradiation. A linear relationship 31 Horie et al 32 Sakurai et al 35 ∆n D = + 0.030…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%
“…Horie et al examined thin films doped with phenylazide and observed Δ n D after photoirradiation of +0.0161. Sakurai et al reported that n D of thin film doped with N -acetyl-α-dehydroarylalanine naphthyl ester increased by about +0.02 after photoirradiation. Very recently, Kern et al , recently examined the photo-Fries rearrangement of polymer and found Δ n D values in the range between +0.042 and +0.070.…”
Section: Introductionmentioning
confidence: 99%